Framing a New Standard for Teaching in Alberta (Alberta Journal of Educational Research, 2013)
A research panel asked to frame the discussion for a new Teaching Quality Standard in Alberta assumes this task requires a paradigm shift away from the status quo efficiency movement. As a member of the panel, the author provides an analysis of paradigm shifts in education and recounts important lessons to be learned. The author challenges the notion that the alternative paradigm posed by an emerging knowledge society provides the best framework to define quality teaching. To accentuate the centrality of relationships, the author offers culture-making as a preferred paradigm where who teachers are is valued as much as what teachers do. Un groupe de recherche à qui on a demandé de délimiter une discussion sur une nouvelle norme pour la qualité de l’enseignement en Alberta part du principe que la tâche exige que l’on délaisse le mouvement actuel prônant l’efficacité. L’auteur, membre de ce groupe de recherche, analyse les changements de paradigme en éducation et rappelle les leçons importantes à tirer de cette évolution. L’auteur conteste la notion que le paradigme alternatif que pose la société de la connaissance émergeante constitue la meilleure base sur laquelle axer l’enseignement de qualité. Il propose plutôt un paradigme reposant sur la création de la culture selon lequel les enseignants sont appréciés pour ce qu’ils sont autant que pour ce qu’ils font.